2017
DOI: 10.1182/bloodadvances.2017004960
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow sites differently imprint dormancy and chemoresistance to T-cell acute lymphoblastic leukemia

Abstract: Key Points BM niches differentially support T-ALL. BM niches differentially protect T-ALL cells from chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 36 publications
4
42
0
Order By: Relevance
“…Additionally, daunorubicin is another important chemotherapeutic for leukemias and adipocytes enhance survival of acute lymphoblastic leukemia cells by secreting factors which protect the tumor cells from oxidative stress, as well as by accumulating and inactivating significant amounts of daunorubicin [103, 104]. Lastly, human T-cell acute lymphoblastic leukemia (T-ALL) cancer cells transplanted into mice accumulate in gonadal adipose tissue of mice and adopt enhanced chemoresistance profiles similar to T-ALL cells in bone marrow sites rich in adipocytes, and adipose T-ALL cells furthermore became more resistant to vincristine when co-cultured with adipocytes in vitro [105]. These studies further highlight the dynamic nature of adipocytes and interaction with other cells beyond metabolism.…”
Section: Antiretroviral Therapy and Adipose Tissuementioning
confidence: 99%
“…Additionally, daunorubicin is another important chemotherapeutic for leukemias and adipocytes enhance survival of acute lymphoblastic leukemia cells by secreting factors which protect the tumor cells from oxidative stress, as well as by accumulating and inactivating significant amounts of daunorubicin [103, 104]. Lastly, human T-cell acute lymphoblastic leukemia (T-ALL) cancer cells transplanted into mice accumulate in gonadal adipose tissue of mice and adopt enhanced chemoresistance profiles similar to T-ALL cells in bone marrow sites rich in adipocytes, and adipose T-ALL cells furthermore became more resistant to vincristine when co-cultured with adipocytes in vitro [105]. These studies further highlight the dynamic nature of adipocytes and interaction with other cells beyond metabolism.…”
Section: Antiretroviral Therapy and Adipose Tissuementioning
confidence: 99%
“…In contrast to MAT's supportive function of normal hematopoiesis during leukemia, its role in leukemia development is controversial and might be lineage specific. Thus, MAT was found to negatively affect T-ALL proliferation in vitro and in vivo thereby mediating chemoresistance [60]. On the other hand, MAT supported the survival and proliferation of AML blasts from patients [61] by hijacking the metabolism of adipocytes to induce free fatty acid release via activation of lipolysis [61].…”
Section: Mat In Malignant Hematopoiesismentioning
confidence: 99%
“…The discovery of the micro environmental effect on the fate of stem cells (7)(8)(9)(10)(11)(12)(13) gave rise to the concept of "quiescent"-now widely considered to be a "dormant-like cell" in the bone marrow (14,15). Studies on the interplay between microenvironment and cancer proliferation have suggested additional prognostic factors such as cell cycle and metabolismrelated chemo-resistant heterogeneity in cancers (16)(17)(18). In T-cell acute lymphoblastic leukemia (T-ALL), for example, various bone marrow niches differentially protect T-ALL cells from chemotherapy by inducing quiescence (18).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the interplay between microenvironment and cancer proliferation have suggested additional prognostic factors such as cell cycle and metabolismrelated chemo-resistant heterogeneity in cancers (16)(17)(18). In T-cell acute lymphoblastic leukemia (T-ALL), for example, various bone marrow niches differentially protect T-ALL cells from chemotherapy by inducing quiescence (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation